The Influence Of The Peer Teaching Learning Model On Learning Outcomes Of Basic Pencak Silat Front Kick Techniques - Ai faridah; Acep Ruswan; Dian Permana; Arief Adhitia Hamzah; Bela Santika; Mutiara Nadhifah (Departement of Mathematics Education, 2024)
This research aims to determine the effect of the peer teaching learning model on the learning outcomes of basic pencak silat front kick techniques in class VII at SMPN 3 Purwakarta. The sample in this study was 32 students from class VII E at SMPN 3 Purwakarta taken using a purposive sampling technique. This research uses a quantitative approach with experimental research methods and pre-experimental design research with pre-test and post-test design types. The independent variable in this research is the Peer Teaching learning model while the dependent variable is the result of learning the basic pencak silat front kick technique. In this study, the pencak silat front kick test was used with an observation sheet as the instrument. Statistical calculations using SPSS 25. Data processing shows that the significance value is (0.00) < 0.05, so HO is rejected and H1 is accepted, which means that there is an influence of the peer teaching learning model on the learning outcomes of pencak silat front kicks in Class VII SMPN 3 Purwakarta. Therefore, because it is felt that it is important to vary learning models, the research aims to provide an alternative Peer Teaching learning model that can be chosen by physical education teachers on the basic techniques of pencak silat front kicks and researchers who are interested in researching the Peer Teaching learning model are advised to further develop it.